Análisis de dos fragmentos de un objeto textil tridimensional de la tumba del “Señor de Sipán”, Perú - Farke, Heidemarie (Zeitschrift für Archäologie Außereuropäischer Kulturen, 2023)
Moche portrait-vessels often depict men wearing 3-dimensional headgears with animal atributes attached to the cloths. In the archaeological record those items normally are represented only by the animal heads and feet made of metal sheet. So, it was fortunate that among the textiles recovered in 1987 from the tomb of the “Lord of Sipán” there were fragments most probably belonging to such a headgear. Conservation was far from being good, and so this article is limited to a detailed analysis of the fragmented textiles, organics and metal pieces used to build up the inner frame of this extraordinary finding.The article will be available as a PDF in the near future.